Hubungan Kemampuan Literasi Membaca Dengan Kemampuan Menyelesaikan Soal Cerita Matematika Kelas IV SDN Buluh 1 - Erlina Dwi Arianti; Rika Wulandari (Universitas Maritim AMNI Semarang, 2023)
The purpose of this study was to determine the relationship between students' literacy skills and the ability to solve math story problems in class IV at SDN BULUH 1. The research approach used in this study was quantitative research with a correlational type of research. The sampling technique uses non-probability sampling, namely the total sample. The research instrument used was a test sheet. Before the test instruments are used in research, they must first carry out validity tests, reliability tests, item difficulty tests, and discriminating power tests so that the test instruments used in research are appropriate for use in the data collection process. The prerequisite test used in this study is the normality test and linearity test. Test the hypothesis of this research data using the Pearson Product Moment correlation and determination test. The results of the data hypothesis test showed a significant positive relationship between students' literacy skills and the ability to solve math story problems for grade IV SDN Buluh 1. The results of data analysis using Pearson Product Moment were proven by the acquisition of rcount < rtable = 0.659 < 0.433 with the acquisition of a significance level of 0.001 < 0.05 including the interpretation of the strong category. Meanwhile, the determination test obtained a value of 43.4%. Based on the analysis it was concluded that the relationship between students' literacy skills and the ability to solve math word problems contributed 43.4%. The level of ability to solve math word problems was 43.4% influenced by students' literacy skills, while 56.6% was influenced by other factors.